Selective RET kinase inhibition for patients with RET-altered cancers. (18th April 2018) - Subbiah, V; Velcheti, V; Tuch, B B; Ebata, K; Busaidy, N L; Cabanillas, M E; Wirth, L J; Stock, S; Smith, S; Lauriault, V; Corsi-Travali, S; Henry, D; et al.
Abstract: Background: Alterations involving the RET kinase are implicated in the pathogenesis of lung, thyroid and other cancers. However, the clinical activity of multikinase inhibitors (MKIs) with anti-RET activity in RET -altered patients appears limited, calling into question the therapeutic potential of targeting RET. LOXO-292 is a selective RET inhibitor designed to inhibit diverse RET fusions, activating mutations and acquired resistance mutations. Patients and methods: Potent anti-RET activity, high selectivity, and central nervous system coverage were confirmed preclinically using a variety of in vitro and in vivo RET-dependent tumor models. Due to clinical urgency, two patients with RET -altered, MKI-resistant cancers were treated with LOXO-292, utilizing rapid dose-titration guided by real-time pharmacokinetic assessments to achieve meaningful clinical exposures safely and rapidly. Results: LOXO-292 demonstrated potent and selective anti-RET activity preclinically against human cancer cell lines harboring endogenous RET gene alterations; cells engineered to express a KIF5B-RET fusion protein −/+ the RET V804M gatekeeper resistance mutation or the common RET activating mutation M918T; and RET- altered human cancer cell line and patient-derived xenografts, including a patient-derived RET fusion-positive xenograft injected orthotopically into the brain. A patient with RET M918T-mutant medullary thyroid cancer metastatic to the liver and an acquired RET V804M gatekeeper resistance mutation, previously treated with six MKI regimens, experienced rapid reductions in tumor calcitonin, CEA and cell-free DNA, resolution of painful hepatomegaly and tumor-related diarrhea and a confirmed tumor response. A second patient with KIF5B-RET fusion-positive lung cancer, acquired resistance to alectinib and symptomatic brain metastases experienced a dramatic response in the brain, and her symptoms resolved. Conclusions: These results provide proof-of-concept of the clinical actionability of RET alterations, and identify selective RET inhibition by LOXO-292 as a promising treatment in heavily pretreated, multikinase inhibitor-experienced patients with diverse RET -altered tumors.